Authentic recipes from Korea - Injoo, Chun (Periplus, 2004)
More than 60 treasures of Korean cooking are revealed through easy-to-follow recipes and beautiful photographs. Learn from leading Korean chefs how to create all-time favorites like beef bulgolgi, chicken and ginseng, and spicy kimchi, as well as other delicious and easy-to-prepare dishes such as gujeolpan (nine-sectioned royal platter), bibimbap (steamed rice with vegetables and red chili paste), and Korean Thanksgiving rice cakes. Adding to the reader's enjoyment are stunning location photography, detailed information on ingredients, and insights into Korean culture.